(untitled) (Research, Society and Development, 2021)
The brown stink bug is considered the main soybean pest species in Brazil, as it has a wide geographic distribution predominating in the midwest and northern regions of Paraná and greater tolerance to chemical insecticides. Thus, this study aimed to evaluate the lethal time and residual period of insecticides in nymphs and adults of the stink bug. The insecticides lambda-cyhalothrin + thiamethoxam, imidacloprid, imidacloprid + bifenthrin, bifenthrin and acephate were used, and in sequence the nymphs and the adult stink bug were subjected to these insecticides to determine the lethal time and residual period. The insecticides Imidacloprido + Bifentrina and Lambda-cyialotrina + Tiametoxam are the most efficient for the control of nymphs and adults of E. heros because they have less lethal time and longer residual period.